OVERVIEW OF RADIATION SAFETY MANAGEMENT SYSTEM IN RADIOLOGY FACILITY OF PETALA BUMI REGIONAL GENERAL HOSPITAL - T.Mohd Yoshandi; Andre Saputra; Devi Purnamasari (Medical Imaging and Radiation Protection Research Journal, 2022)
The radiation safety management system consists of seven components that must be implemented, namely radiation protection organization, radiation dose monitoring and radioactivity monitoring, radiation protection equipment, medical checks up, document archiving, quality assurance, and education and training. This study aims to determine whether or not the seven components have been fulfilled. The type of research conducted in this study is descriptive with a qualitative approach. The results show that the radiology facility of Petala Bumi Regional Hospital has fulfilled most of the components.